Bird procurement by humans during the Middle and early Upper Paleolithic of Europe: New data for the Aurignacian of southwestern France. (30th March 2020) - Laroulandie, Véronique; Morin, Eugène; Soulier, Marie-Cécile; Castel, Jean-Christophe
Abstract: Recently, the development of taphonomically-oriented studies of avifaunal assemblages have contributed towards renewing our perceptions of the complexity of Neandertal behavioral adaptations in Europe. In contrast, few studies have been conducted on bird samples dated to the Early Upper Paleolithic. Here, we provide new data for three archeological sites (Isturitz, le Piage, Abri Cellier) from southwestern France that have produced Aurignacian material. Evidence of bird processing, use of raptor talons and that bird bones served as raw material aid in enlarging our knowledge of how birds were exploited during the Aurignacian. Overall, the available information shows a clear focus on scavenging birds and points to only marginal changes in the way humans used birds during the Mousterian and Early Upper Paleolithic.